Comparison of Hemodynamic Performance and Clinical Results with EVAHEART Versus HeartMate II. Issue 5 (September 2017) - Matsumoto, Yorihiko; Fujita, Tomoyuki; Fukushima, Satsuki; Hata, Hiroki; Shimahara, Yusuke; Kume, Yuta; Yamashita, Kizuku; Kuroda, Kensuke; Nakajima, Seiko; Sato, Takuma; Seguchi, Osamu; Yanase, Masanobu; et al.
Abstract : This study aimed to compare the hemodynamic performance and clinical results of the EVAHEART and HeartMate II left ventricular assist devices (LVADs). From 2007 to 2016, fourteen patients received EVAHEART and 28 received HeartMate II at our center. Early survival, driveline infection, and neurologic events were evaluated. Hemodynamic performance was evaluated with transthoracic echocardiography and right heart catheterization. Mean follow-up was 35.5 ± 14.8 months for EVAHEART and 29.8 ± 6.5 months for HeartMate II. Survival rates were comparable between the two groups. After 24 months, freedom from driveline infection was 28% with EVAHEART, and 85% with HeartMate II; freedom from neurologic events was 21% with EVAHEART, and 89% with HeartMate II. Serum lactate dehydrogenase was significantly lower with EVAHEART. There was a significantly greater decrease in left ventricular size with HeartMate II. In catheter examination performed 1 month postoperatively, HeartMate II recipients had significantly lower pulmonary capillary wedge pressure and mean pulmonary pressure, despite a comparable cardiac index. Both devices provided excellent clinical results and hemodynamic performance. HeartMate II could be a better choice to avoid driveline infection and neurologic events. Our results suggest that HeartMate II reduced right ventricular afterload. However, further analysis of more cases is required.